(untitled) (American Journal of Management, 2024)
Business education emphasizes an analytical approach to decision making and strategy development. However, certain factors, such as Corporate Social Responsibility (CSR), are challenging to quantify in corporate strategy. The consideration of CSR, including Environmental, Social, and Corporate Governance, by Boards of Directors, is among these difficult-to-quantify factors. Business schools now teach students to focus more on a CSR/stakeholder approach, in line with updated standards such as Advance Collegiate Schools of Business Standard 9, which has increased the focus on societal impact in curricula. The CSR/stakeholder approach has emerged as a global strategic management option but is not without challenges, including non-homogeneous CSR issues and potential greenwashing. Moreover, a measurable stakeholder approach might lead to decreased profitability. Individual differences, particularly among millennials, influence support for or against CSR initiatives. This paper evaluates these differences and their impact on decision-making, which will significantly influence society as millennials rise to leadership roles.